Transcriptome-wide identification and characterization of WUSCHEL-related homeobox (WOX) gene family in Pinus yunnanensis - Junfei Xu; Zhaoliu Hu; Sili Chen; Junrong Tang; Lin Chen; Peizhen Chen; Nianhui Cai; Yulan Xu (BMC Genomics)
Abstract WUSCHEL-related homeobox (WOX), a specific gene family in plants, plays a critical role during stem cell regulation, plant regeneration and upgrowth. However, our understanding of WOX functions in conifers is limited compared to angiosperms. To address this gap, we investigated the presence, expression profiles and protein characteristics of WOX gene in P. yunnanensis. Our findings revealed that 10 PyWOX genes were dispersed across three existing clades, and their expression profiles were presented in specific developmental stages and tissues. The ancient-clade members (PyWOX13, PyWOXG, PyWOXA) exhibited constitutive expressions in most tissues and developmental stages, indicating that they are the oldest and conserved WOX genes. Members of the intermediate-clade (PyWOXB, PyWOXE) were primarily expressed during callus formation and seed germination, suggesting a role in promoting embryogenesis and plant regeneration. Most members of WUS-clade (PyWUS, PyWOX3, PyWOX4, PyWOX5, PyWOXX) showed high transcripts level in cluster buds, which may be related to meristematic development and the formation of axillary meristems. The self-activation assay demonstrated that PyWOX4 has transcriptional activation activity. Our study also suggested that there were highly conserved and clear orthologs of WOX genes present in Pinus. Together, these findings provide a foundation for further clarifying the function and regulatory mechanism of WOX genes in P. yunnanensis growth and development.